Himala - Lee, Ricardo; Bernal, Ishmael; Jarlego, Ike.; Carballo, Bibsy M.; Concio, Charo Santos-.; Aunor, Nora.; Experimental Cinema of the Philippines ([Manila] Experimental Cinema of the Philippines, 1982)
Story of a young woman believed to have miraculous powers who transforms a sleepy barrio into a commercial center.
VHS Hi-fi
Production designer, Raquel N. Villavicencio ; film editor, Ike Jarlego, Jr. ; sound supervision, Vic Macamay ; produced by Bibsy M. Carballo ; executive producer, Charo Santos-Concio.
Nora Aunor.
Keywords: Miracle workers -- Philippines -- Drama; Miracles -- Philippines -- Drama; Feature films -- Philippines